An Overview Analysis of Metaphors for God in Davidic Psalms Based on the New International Version of the Holy Bible - Silalahi, Ronald Maraden Parlindungan; William; Willy (Journal of English Teaching as a Foreign Language, 2020)
Basically words, phrases, clauses, and sentences are metaphorical forms because they are generated through a process of symbolization. This symbolization process presents objects outside the human mind in forms that are conventionally interpreted together. This can also be seen in the spiritual objects that are presented in religious traditions. One of the symbolic objects that are often presented in religious traditions is God. The scriptures present God in various symbolic forms which reflect spiritual qualities and values. This article aims to explore how the metaphors for God in the Holy Bible, especially in Davidic Psalms, explain the many attributes of God. The Book of Psalms is one of the longest books in the Bible. The Psalms contain songs composed by David as a form of his spiritual closeness to God. The Book of Psalms contains a lot of figurative expressions and it includes metaphors for God. Metaphors are analyzed textually by considering the underlying social and cultural aspects. The version of the Bible that is used in this research is the New International Version. The method that this research used is textual analysis from selected texts in the Book of Psalms in the Old Testament where the metaphors for God are apparent.